2012
DOI: 10.5455/ijavms.133
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION, IDENTIFICATION AND ANTIBIOGRAM OF Pasteurella multocida ISOLATES OF RABBITS SUFFERING FROM PASTEURELLOSIS

Abstract: Isolation of Pasteurella multocida was attempted from the heart blood, spleen, liver and lung collected from rabbits (4 No,s) suspected to have died of pasteurellosis. A total of four P. multocida isolates were isolated and identified on the basis of biochemical characteristics, pathogenicity studies in mice and PM-PCR. The In vitro antibiotic sensitivity test of the organisms was conducted which revealed that all the four isolates showed sensitivity to Gentamicin and Oflaxacin. Three of them were sensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 6 publications
9
12
0
Order By: Relevance
“…Pasteurella multocida has been isolated from the heart blood, spleen, liver and lung collected from turkeys and chicken, suspected to have died of avian pasteurellosis (Balakrishnan and Roy, 2012). The biochemical tests were positive for indole production, oxidase and catalase production coinciding with the earlier findings of Quinn et al, (1994) and Kawamota (1990).…”
Section: Resultssupporting
confidence: 57%
“…Pasteurella multocida has been isolated from the heart blood, spleen, liver and lung collected from turkeys and chicken, suspected to have died of avian pasteurellosis (Balakrishnan and Roy, 2012). The biochemical tests were positive for indole production, oxidase and catalase production coinciding with the earlier findings of Quinn et al, (1994) and Kawamota (1990).…”
Section: Resultssupporting
confidence: 57%
“…The highest estimate of heritability was found for pods per plant 74.2% followed by plant height 65.8% while lowest for days taken to maturity 48.8% followed by biomass per plant 47.1% 2,11,13 . The estimate of genetic advance was found for pods per plant 8.5906% followed by plant height 3.9001% while lowest for primary branches per plant 0.088% followed by seeds per plant 0.0686% 5,6,15,18,17 . The higher estimates of heritability and genetic advance indicated that the selection on the basis of these traits may be useful for the improvement of yield.…”
Section: Resultsmentioning
confidence: 97%
“…A negative and significant association occurred between the days to maturity with plant height, seeds per pod, and 100-seed weight. Grains per plant were positively and significantly correlated with days to maturity 1,3,6,24,29,16 .…”
Section: Correlationmentioning
confidence: 92%
See 2 more Smart Citations